Search for an axion-like particle in radiative J/ψ decays - M. Ablikim; M.N. Achasov; P. Adlarson; R. Aliberti; A. Amoroso; M.R. An; Q. An; Y. Bai; O. Bakina; R. Baldini Ferroli; I. Balossino; Y. Ban; et al. (Physics Letters B, 2023)
We search for an axion-like particle (ALP) a through the process ψ(3686)→π+π−J/ψ, J/ψ→γa, a→γγ in a data sample of (2.71±0.01)×109 ψ(3686) events collected by the BESIII detector. No significant ALP signal is observed over the expected background, and the upper limits on the branching fraction of the decay J/ψ→γa and the ALP-photon coupling constant gaγγ are set at 95% confidence level in the mass range of 0.165≤ma≤2.84GeV/c2. The limits on B(J/ψ→γa) range from 8.3×10−8 to 1.8×10−6 over the search region, and the constraints on the ALP-photon coupling are the most stringent to date for 0.165≤ma≤1.468GeV/c2.